TRAINING THE TEACHER CANDIDATES A GOOD CLASSROOM MANAGEMENT TO IMPROVE THEIR PROFICIENCIES - Sulistyowati, Titis; Kurniati, Diah (Language Circle: Journal of Language and Literature, 2014)
Teaching Practice program (PPL) must be done by the students of English Education Department of Muria Kudus University as one of the requirements to finish their study of under graduate program in English Education. PPL implementation is done in some schools that have been determined before by the department. PPL is a training program for students which offer an opportunity for the students to apply the theory and their knowledge about education as well as the implementation of English teaching directly in front of the students at schools where they have to do the PPL. As teacher trainees, the English Education Department students, do not have sufficient experience in managing a class, especially in providing effective instruction in the classroom. Providing good instructions is one of the important aspects of the success of the learning process, so it is important for teachers to understand how to organize the lesson and provide classroom interaction in a proper and effective way. The focus of this study is to explain how the classroom management techniques applied by the teacher candidates (PPL) in teaching and learning and the improvements of the students during the lesson. As the PPL program manager, Department of English Education of UMK can use this study as an evaluation by understanding the weaknesses and problems experienced by students teacher during teaching practice program, so the Department will be able to make better achievement through the implementation of the program so that students will be well prepared to carry out the teaching process in the classroom.